Garra zubzaensis, a new fish species (Cyprinidae: Labeoninae) from the Brahmaputra River basin, Nagaland, North-Eastern India - Tenali, Diamond Rajakumar; Shangningam, Bungdon; Bhattacharjee, Pampa; Patel, Arun Bhai; Kosygin, Laishram (Zootaxa, 2024)
A new species of Garra (Labeoninae) is described from the Zubza River, a headwater of the Brahmaputra River basin, in Kohima district of Nagaland, North-eastern India. The new species is distinguished by the following combination of characters: a black spot located on the principal ray and first three branched rays of the dorsal (upper) lobe distal part, as well as a black submarginal V-shaped band on the principal ray and whole branched rays of the ventral (lower) lobe of caudal fin; snout with weakly-developed proboscis represented by slightly upwards elevated hump, with no transverse groove and no transverse lobe, and with 10–12 small tubercles on anterodorsal marginal aspect; 34 lateral-line scales including two pored scales on caudal fin; absence of scales on chest and presence of poorly developed scales on belly; relatively shorter caudal peduncle (10.7–12.5 % SL), and snout (34–35 % HL); and relatively larger eye (31–32 % HL).